2015
DOI: 10.4995/agt.2015.3584
|View full text |Cite
|
Sign up to set email alerts
|

The dynamical look at the subsets of a group

Abstract: <p>We consider the action of a group $G$ on the family $\mathcal{P}(G)$ of all subsets of $G$ by the right shifts $A\mapsto Ag$ and give the dynamical characterizations of thin, $n$-thin, sparse and scattered subsets.</p><p>For $n\in\mathbb{N}$, a subset $A$ of a group $G$ is called $n$-thin if $g_0A\cap\dots\cap g_nA$ is finite for all distinct $g_0,\dots,g_n\in G$.<br />Each $n$-thin subset of a group of cardinality $\aleph_0$ can be partitioned into $n$ $1$-thin subsets but there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Is X orbitally discrete? For finite partitions of an n-thin space into discrete subspaces, see [5], [14], [17], [1, Section 6]. 2.…”
Section: Resutsmentioning
confidence: 99%
“…Is X orbitally discrete? For finite partitions of an n-thin space into discrete subspaces, see [5], [14], [17], [1, Section 6]. 2.…”
Section: Resutsmentioning
confidence: 99%
“…The action of the group G extends to a continuous action of G on the Stone-Čech compactification βX of the discrete space X. The remainder X * = βX \ X is an invariant subset of the action, so we obtain a dynamical system (X * , G) and can study the interplay between properties of the coarse structure E G and the properties of the dynamical system (X * , G), see the papers [19], [24], [30] for more information on this topic. By a dynamical system we understand a compact Hausdorff space K endowed with the continuous action of some group G.…”
Section: Coarse Structures and Topological Dynamicsmentioning
confidence: 99%
“…Given a countable subgroup G ⊆ S ω , consider the finitary coarse structure E G on ω induced by the action of the group G. By analogy with Theorem 4.1 [19], it can be shown that for any P -point p ∈ ω * the set p coincides with the closure Gp of the orbit of p under the action of the group G on ω * . Problem 5.8 ( [19]). Is a free ultrafilter p on ω a P -point if p = Gp for any countable subgroup G ⊆ S ω ?…”
Section: Problem 57 ([21]mentioning
confidence: 99%
“…Let G be an arbitrary infinite group. In [15], we constructed two injective sequences (x n ) n∈ω , (y n ) n∈ω in G such the set {x n y m : 0 ≤ n ≤ m < ω} is scattered. By Theorem 4.3(ii), this subset is not sparse.…”
Section: The Dynamical Look At the Subsets Of A Groupmentioning
confidence: 99%